The effect of earnings smoothness on manufacturing companys performance - Riani Yandiarti (The Indonesian Accounting Review, 2013)
The purpose of this study is to determine empirically the effect of earnings smoothnesson companys performance. The companys performance used in this study is based ontwo indicators of the company's operational performance (ROA) and market performance(Tobin's Q). In addition to earnings smoothness as the independent variable andcompanys performance as the dependent variable, this study also uses the controlvariable leverage and size. The sample used in this study based on the criteria of samplingas many as 96 manufacturing companies listed in Indonesia Stock Exchangeduring the years of 2005-2010 so that the number of data samples 576. According toanova F test in linear regression show that models of regression can be used to predictthe company's operational performance and market performance. While the results ofthe anova t test in linear regression show that earnings smoothness significantly affectthe market performance. However, earnings smoothness does not significant affect thecompany's operational performance. Control variables are leverage and size resultsshow the opposite of the independent variable smoothness profit, that significantlyinfluence the company's operational performance (ROA) but not significantly withmarket performance (Tobin's Q).